Adsorption of water from aqueous acetonitrile on silica-based stationary phases in aqueous normal-phase liquid chromatography - Soukup Jan; Jandera Pavel (Elsevier Science BV, 2014)
Excess adsorption of water from aqueous acetonitrile mobile phases was investigated on 16 stationary phases using the frontal analysis method and coulometric Karl–Fischer titration. The stationary phases include silica gel and silica-bonded phases with different polarities, octadecyl and cholesterol, phenyl, nitrile, pentafluorophenylpropyl, diol and zwitterionic sulfobetaine and phosphorylcholine ligands bonded on silica, hybrid organic-silica and hydrosilated matrices. Both fully porous and core-shell column types were included. Preferential uptake of water by the columns can be described by Langmuir isotherms. Even though a diffuse rather than a compact adsorbed discrete layer of water on the adsorbent surface can be formed because of the unlimited miscibility of water with acetonitrile, for convenience, the preferentially adsorbed water was expressed in terms of a hypothetical monomolecular water layer equivalent in the inner pores. The uptake of water strongly depends on the polarity and type of the column. Less than one monomolecular water layer equivalent was adsorbed on moderate polar silica hydride-based stationary phases, Ascentis Express F5 and Ascentis Express CN column at the saturation capacity, while on more polar stationary phases, several water layer equivalents were up-taken from the mobile phase. The strongest affinity to water was observed on the ZIC cHILIC stationary phases, where more than nine water layer equivalents were adsorbed onto its surface at its saturation capacity. Columns with bonded hydroxyl and diol ligands show stronger water adsorption in comparison to bare silica. Columns based on hydrosilated silica generally show significantly decreased water uptake in comparison to stationary phases bonded on ordinary silica. Significant correlations were found between the water uptake and the separation selectivity for compounds with strong polarity differences.
Adsorpce vody z vodného acetonitrilu na stacionionárních fázích založených na silikagelu v kapalinové chromatografii v normální fázi s vodně organickou mobilní fází
Keywords: Adsorption of water; Hydrophilic interaction chromatography; HILIC stationary phases; Adsorpce vody; hydrofilní interakční chromatografie; HILIC stacionární fáze